Hubungan Pengetahuan dan Sikap terhadap Seks Pra Nikah Pada Remaja Cabang Tiberias II Rumahtiga : The Relationship between Knowledge and Attitudes towards Premarital Sex in Teenagers at Tiberias II Rumahtiga Branch - Djurumana, Yohana; Debora Harsono; Minnalia Soakakone (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2025)
Premarital sex is a common social phenomenon that can have negative impacts on physical health, mental health, and social relationships. This study uses a quantitative method with a survey approach involving respondents from the youth congregation of Tiberias II Rumahtiga Branch. The aim of this study is to analyze the factors related to premarital sex among the youth congregation of Tiberias II Rumahtiga Branch, namely knowledge, attitudes, and parental support. Data were collected through questionnaires distributed to respondents and analyzed using statistical tests to determine the relationship between independent and dependent variables. The sampling technique used is total sampling, with a sample size of 40 people. The data analysis technique used is the Chi-Square test. The results show that all variables have a relationship with a p-value of < 0.05. Knowledge related to premarital sex, attitudes, and parental support are protective factors against premarital sex behavior. However, the environment and social media can influence the sexual behavior of adolescents to engage in premarital sex. Based on these findings, it is recommended to increase religious education and strengthen moral values among the youth congregation to prevent premarital sex behavior.